PENGARUH KERAGAMAN PRODUK, KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA APOTEK ANGGREK KPRI RSUD SITUBONDO - Pandango, Herlina; Soeliha, Siti; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the effect of product diversity, service quality and price on customer loyalty with customer satisfaction as an intervening variable at Anggrek KPRI Pharmacy, Situbondo Regional Hospital. The sampling technique is determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Product diversity has a negative but insignificant effect on Customer Satisfaction, Service quality has a significant positive effect on Customer Satisfaction, Price has a significant positive effect on Customer Satisfaction, Product diversity has a positive but insignificant effect on Customer Loyalty, Service quality has a negative but insignificant effect on Customer Loyalty, Price has a positive but insignificant effect on Customer Loyalty, Customer satisfaction has a significant positive effect on Customer Loyalty, Product diversity has a negative but insignificant effect on Customer Loyalty through Customer Satisfaction, Service quality has a positive but insignificant effect on Customer Loyalty through Customer Satisfaction, Price has a significant positive effect on Customer Loyalty through Customer Satisfaction.